ANALISIS SISTEM PROTEKSI KEBAKARAN AKTIF PADA COAL HANDLING SYSTEM PT PEMBANGKITAN JAWA BALI DI BALIKPAPAN - Nuryanto, Nuryanto; Ramdan, Muhamad; Anisyah, Rizky Siti (IDENTIFIKASI, 2023)
The Coal Handling System is a system to handle everything from unloading coal from barges to stockpiling coal at PLTU Kaltim Teluk. The fire hazard in the coal handling system can be triggered by the large amount of coal fuel, coal dust and the potential for self-ignition to coal dust explosions. Active fire protection systems make a major contribution to the success of fire management. Therefore, it is necessary to have an overview of the application of an active protection system and the level of compliance with NFPA standards which include: NFPA 10, NFPA 13, NFPA14, NFPA20, NFPA72, NFPA850. The type of research used is descriptive qualitative with data collection: observation and interviews. Assessment of the results of the existing suitability will be assessed using a descriptive percentage calculation. The results showed that of the 7 variables with 63 elements discussed, 93% were in accordance with the standard and 4 elements (7%) were not met. Based on the fire audit assessment level of the Research and Development Center of the Ministry of Public Works, the results are in the criteria of Good or have met the requirements.